Efficacy and influencing factors of the four‐step approach combining the situational simulation teaching method in the clinical practice of standardized training for residents. Issue 5 (8th September 2022) - Shan, Tong; Kejun, Wang; Ying, Feng; Jia, Huang; Hongyan, Jiang
Abstract: Background and Aims: Clinical skills practice is an essential component in standardized residency training. However, traditionally skill training methods are dogmatic and not all residents are exposed to such prescribed situations during their residency. The aims of this study were to evaluate the effectiveness and influence factors of a four‐step approach combining situational simulation teaching methods in clinical practice for residents. Methods: Enrolled all second‐year residents from the internal medicine base between May 2017 and May 2018 ( n  = 94), randomly divided into two groups. Forty‐eight residents were selected as experimental group, while the others 46 as the control group. Adopted traditional clinical practice method in the teaching and assessment of the control group, while used four‐step approach combining situational simulation teaching method in experimental group. We compared the theoretical and skill assessment scores in preclass and postclass. Conducted a satisfaction survey after class and analyzed the influencing factors of the teaching effect evaluation. Results: There were no significant differences in the theoretical and skill assessment scores between experimental group and control group at the beginning. After the class, both the average skill assessment and Direct Observation of Procedural Skills scores of the experimental group were higher than those of the control. Satisfaction survey findings identified that the experimental group expressed higher satisfaction. Logistic regression showed that educational background, "situational simulation mode helps to improve clinical skills training, " "helps to maintain attention during learning, " and "helps improve the ability to exercise analysis and solve problems" were the influencing factors of learners' satisfaction. Conclusion: The application of four‐step approach combining situational simulation teaching methods in the clinical practice of residents can significantly improve skills, thinking ability, decision‐making ability, and teaching satisfaction. Therefore, four‐step approach combining situational simulation teaching methods is worth promoting in teaching clinical skills for internal medicine residency training.